Measurement of vadose zone water content with direct-push nuclear magnetic resonance logging - Gordon Osterman; Rosemary Knight (Environmental Research Communications)
Predicting the efficiency of managed aquifer recharge (MAR) operation requires understanding the distribution of sediment type and water content in the vadose zone. In this study we assess the use of a direct-push nuclear magnetic resonance logging technique which can rapidly image water content profiles without the need for permanent boreholes. By combining nuclear magnetic resonance logging with direct-push sediment texture logging using cone penetrometer testing, it is possible to estimate the water content in the vadose zone and relate differences in water content to sediment type. We demonstrate this approach using four co-located nuclear magnetic resonance and cone penetrometer testing logs acquired to depths of approximately fifteen meters at an active almond orchard in California’s Central Valley. The results show water contents typically greater than 25% in clay- and silt-rich sediments, and up to 10% in sand-rich sediments. The ability to rapidly assess sediment type and water content using two direct-push tools opens up many exciting opportunities to study complex groundwater systems, even active orchards and other agricultural environments.